Prepectoral Implant-Based Breast Reconstruction: Rationale, Indications, and Preliminary Results. Issue 2 (February 2017) - Sigalove, Steven; Maxwell, G. Patrick; Sigalove, Noemi M.; Storm-Dickerson, Toni L.; Pope, Nicole; Rice, Jami; Gabriel, Allen
Abstract : Summary: Implant-based breast reconstruction is currently performed with placement of the implant in a subpectoral pocket beneath the pectoralis major muscle, by means of the dual-plane approach. Although the safety and breast aesthetics of this approach are well recognized, it is not without concerns. Animation deformities and accompanying patient discomfort, which are direct consequences of muscle elevation, can be severe in some patients. Moving the implant prepectorally may eliminate these concerns. For a successful prepectoral approach, the authors advocate use of their bioengineered breast concept, which was detailed in a previous publication. In this report, the authors discuss the rationale for prepectoral implant reconstruction, its indications/contraindications, and preliminary results from over 350 reconstructions. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.